Progress in biomass gasification technique - with focus on Malaysian palm biomass for syngas production - Samiran, N. A. (Elsevier Ltd, 2016)
Synthesis gas, also known as syngas, produced from biomass materials has been identified as a potential source of renewable energy. Syngas is mainly consists of CO and H2, which can be used directly as fuel source for power generation and transport fuel, as well as feedstock for chemical production. Syngas is produced through biomass gasification process that converts solids to gas phase via thermochemical conversion reactions. This paper critically reviews the type of gasifiers that have been used for biomass gasification, including fixed bed, fluidized bed, entrained flow and transport reactor types. The advantages and limitations of these gasifiers are compared, followed by discussion on the key parameters that are critical for the optimum production of syngas. Depending on the biomass feedstock, the properties and characteristics of syngas produced can be varied. It is thus essential to thoroughly characterise the properties of biomass to understand the limitations in order to identify the suitable methods for gasification. This paper later focuses on a specific biomass - oil palm-based for syngas production in the context of Malaysia, where palm biomass is readily available in abundance. The properties and suitability for gasification of the major palm biomass, including empty fruit bunch, oil palm fronds and palm kernel shells are reviewed. Optimization of the gasification process can significantly improve the prospect of commercial syngas production.